Ibn Sina's theory of attribute monotheism: conceptual unity or semantic unity - یارعلی کرد فیروزجایی (حکمت اسرا)
One of the types of monotheism is monotheism. According to the common view, monotheism refers to the attributes that all the attributes of God and His essence exist in a single existence, although they differ in terms of concepts. But Ibn Sina did not suffice with the unity of attributes and essence in external existence and considered them as one in terms of concept. This view requires the literal synonymy of the attributes and is rejected. The author believes that there is enough evidence in Ibn Sina's words that based on them, it can be said that the conceptual unity of essence and attributes does not necessarily mean their literal synonymy, Ibn Sina does not mean that the attributes that he carries on God They are common in their core, namely, entity and security, and this single unit of proof is the meaning of those attributes, and Ibn Sina refers to the conceptual unity of this semantic unity, not unity in the conceptual-mental approach. Given that in every adjective, in addition to the affirmative meaning of security and existence, there is a certain denial, a special addition or a special denial, and a special addition, it cannot be said that their words are synonymous, and thus the critiques of Ibn Sina's theory. There are no definite criticisms; Because Ibn Sina's theory is neither a literal synonym of attributes nor does it require it.